ANALYZING THE CAUSES OF STUDENTS’ DIFFICULTIES IN ENGLISH SPEAKING AMONG BUSINESS ENGLISH COMMUNICATION STUDENTS - Musdalifah Ahmad; Riny Jefri; Andi Hajar (International Journal of Business English and Communication, 2026)
This study aims to analyse Business English Communication students' difficulties in speaking English with a focus on linguistic and social factors and explore strategies that can be applied to improve their speaking ability. The research method used is qualitative with a descriptive approach, where data is collected through observation, interviews, and questionnaires of purposely selected students. The research stages included planning, data collection, data analysis, and interpretation and conclusion. The results showed that limited vocabulary, pronunciation errors, and grammatical constraints are the main factors that hinder students' fluency in speaking English. In addition, social factors such as low self-confidence and lack of motivation also contribute to their difficulties in communicating effectively. Therefore, creating a supportive learning environment and implementing structured speaking practice can help students overcome these challenges, increase their confidence, and improve their speaking skills.